Pemberdayaan Masyarakat Nelayan Melalui Inovasi Gelindingan Portable sebagai Alat Bantu Pemindahan Perahu yang Efektif dan Efisien - Khikmawati, Liya Tri; Jaya, Made Mahendra; Sarasati, Wulandari; Azis, Muh. Arkam; Satyawan, Noar Muda; Tanjov, Yulia Estmirar; Mainnah, Muth; Suhery, Noveldesra; Sari, Iya Purnama; Larasati, Rakhma Fitria; Suratna, Suratna (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to increase the knowledge and skills of fishermen in Pengambengan village, Jembrana Regency, Bali in creating innovative portable rollers as an effective and efficient tool for moving boats. The method of implementing this service uses training with data collection techniques in the form of observation, interviews and documentation. Evaluation of the success level of this service uses a questionnaire instrument, which is analyzed descriptively and quantitatively. The results of this service activity show that fishermen can understand well the innovation of portable rollers as an effective and efficient tool for moving boats. Apart from that, fishermen have been able to create and improve existing wheel innovations. The finished rolling innovation can be used by fishermen properly and correctly when moving boats/jukungs to places that are safer from high tides.